THE IMPLEMENTATION OF PEER TUTORING IN LEARNING READING FOR EFL LEARNERS - Ade Nursamsul Maarif (Journal of English Education Program (JEEP), 2020)
EFL learners face difficulties in comprehending the reading skill. This paper reports the implementation of peer tutoring for EFL learners in learning reading and EFL learners’ perception towards the implementation of peer tutoring in learning reading. This research employed qualitative case study design. The research participants were thirty six students’ of the eleventh grade at one of high schools in West Java and a teacher who taught at that class. The data were obtained from several sources, those are classroom observation and questionnaire. In analyzing the classroom observation, the researcher transcribed the result of the classroom observation into words. In analyzing the questionnaire, the researcher used percentage computation from close-ended questionnaire which was displayed into the table completed with the description, categorized and also conclusion for each items. The findings revealed that the teacher implemented peer tutoring in learning reading successfully and followed the appropriate steps, the steps are conducted selection of tutoring pairs, gave a task structure, conducted training sessions, prepared tutoring material, conducted feedback error correction and conducted close teacher monitoring. The result of the research also showed that most of the EFL learners’ perceived that peer tutoring is the appropriate method to be applied in learning reading. The use of peer tutoring could make EFL learners more active in learning process, both peer tutor and tutees played an active role in establishing and fostering a collaborative learning relationship, sharing responsibility for much of their own learning experiences. This research concludes that peer tutoring should be applied as teaching method in learning reading, because the EFL learners feel enjoyed and improved their motivation in learning. Finally, the researcher suggests that peer tutoring could be integrated into other skills such as listening, writing and speaking.Keywords: peer tutoring, learning reading, EFL learners, implementation.